Infliximab treatment reduces complement activation in patients with rheumatoid arthritis. Issue 7 (15th June 2005) - Familian, A; Voskuyl, A E; van Mierlo, G J; Heijst, H A; Twisk, J W R; Dijkmans, B A C; Hack, C E
Abstract : Background: Tumour necrosis factor (TNF) blocking agents decrease C reactive protein (CRP) levels in rheumatoid arthritis (RA). It has been shown that CRP may contribute to complement activation in RA. Objective: To assess the effect of intravenous infliximab treatment on complement activation, especially that mediated by CRP, in RA. Methods: 35 patients with active RA (28 joint count Disease Activity Score (DAS28) >4.4) were treated with intravenous injections of infliximab (3 mg/kg, at weeks 0, 2, 6, 14, and 22). Clinical response and plasma levels of complement activation products, of CRP and of CRP-complement complexes, which are specific markers for CRP mediated complement activation, were assessed at the indicated time points up to 22 weeks. The relationship between CRP and CRP-complement complexes was analysed by paired t test between two time points and by generalised estimated equation, to test differences of variables over time. Results: At 2 weeks after the first dose, infliximab significantly reduced overall C3 and C4 activation and plasma levels of CRP and CRP-complement complexes were also significantly reduced at this time point. The effects of infliximab on CRP and complement continued throughout the observation period and were more pronounced in patients with a good response to infliximab treatment. Conclusion: Treatment with infliximab decreases plasma levels of CRP and CRP dependent complement activation products and concomitantly may reduce complement activation in RA. Complement activation may be among the effector mechanisms of TNF in RA.